Sayyed Hossein Nasr’s Critique of Modernity: The Perspective of Perennial Philosophy and Its Relevance to Contemporary Islamic Thought - Maulud, Al; Syaifuddin, Helmi (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2025)
Modernity has not only resulted in advancements in science and technology but has also given rise to fundamental dilemmas within the landscape of contemporary Islamic thought—particularly concerning the crisis of meaning, the marginalization of spirituality, and the dominance of secular epistemology. This article aims to analyze Sayyed Hossein Nasr’s critique of modernity and examine the relevance of the perennial philosophy he proposes in addressing these challenges within the context of contemporary Islamic thought. This study employs a qualitative research method grounded in library research. The approach utilized is philosophical hermeneutics combined with discourse analysis of Nasr’s thought, particularly referencing primary works such as Islam and the Plight of Modern Man. Nasr contends that modernity is inherently reductionist, as it places excessive emphasis on the empirical-material dimension while neglecting the metaphysical aspect and the human connection to transcendent reality. In response, the perennial philosophy he advocates underscores the significance of universal spiritual values, the transcendent unity of religions, and the preservation of tradition as foundational elements for restoring the balance between spirituality and rationality in contemporary life. Unlike previous studies, this article specifically emphasizes the integration of Nasr’s perennial philosophy with the dynamics of contemporary Islamic thought, particularly in addressing the epistemological crisis resulting from the modernization of knowledge. The article contributes to the discourse on the significance of revitalizing spirituality and the Islamic scholarly tradition as a critical and constructive response to the dominance of modernity. Abstrak: Modernitas tidak hanya menciptakan kemajuan dalam bidang ilmu pengetahuan dan teknologi, tetapi juga melahirkan dilema mendasar dalam lanskap pemikiran Islam kontemporer, terutama terkait krisis makna, marginalisasi spiritualitas, dan dominasi epistemologi sekuler. Artikel ini bertujuan untuk menganalisis kritik Sayyed Hossein Nasr terhadap modernitas serta relevansi tawaran filsafat perenial dalam menjawab tantangan-tantangan tersebut dalam konteks pemikiran Islam kontemporer. Penelitian ini menggunakan metode penelitian kualitatif berbasis studi pustaka, pendekatan yang digunakan adalah hermeneutika filosofis dan analisis wacana pemikiran Nasr, dengan merujuk pada karya-karya primer seperti Islam and the Plight of Modern Man. Nasr menilai bahwa modernitas bersifat reduksionis karena terlalu menekankan dimensi empiris-material dan mengabaikan aspek metafisik serta keterhubungan manusia dengan realitas transenden. Sebagai tanggapan, filsafat perenial yang ia tawarkan menekankan pentingnya nilai-nilai spiritual universal, kesatuan transenden agama-agama, dan pelestarian tradisi sebagai fondasi untuk merestorasi keseimbangan antara spiritualitas dan rasionalitas dalam kehidupan modern. Berbeda dari kajian-kajian sebelumnya, artikel ini menyoroti secara spesifik integrasi pemikiran filsafat perenial Nasr dengan dinamika pemikiran Islam kontemporer, khususnya dalam menghadapi krisis epistemologis akibat modernisasi pengetahuan. Artikel ini berkontribusi dalam memperluas diskursus tentang pentingnya revitalisasi spiritualitas dan tradisi keilmuan Islam sebagai respon kritis dan konstruktif terhadap hegemoni modernitas.